Acute effects of unilateral sectioning the superior ovarian nerve of rats with unilateral ovariectomy on ovarian hormones (progesterone, testosterone and estradiol) levels vary during the estrous cycle - Cruz María-Esther; Everardo Pamela M; Mendoza Fernando D; Gallegos Alma I; Velasco Jacqueline; Flores Angélica; Domínguez Roberto (BMC, 2011)
Abstract The present study analyzed the participation of the left and right superior ovarian nerves (SON) in regulating progesterone, testosterone, and estradiol serum levels in unilaterally ovariectomized rats on each day of the estrous cycle. For this purpose, ovarian hormone concentrations in serum were measured in animals with either sham-surgery, unilateral ovariectomy (ULO), unilateral sectioning of the SON, or sectioning of the SON innervation of the in situ ovary in rats with ULO. This investigation results show that the right and left ovaries have different capacities to maintain normal hormone levels, that such capacity varies during the estrous cycle, and that it depends on the integrity of the SON innervation. In rats with only one ovary, the effects of ovarian denervation on hormone levels varied according to which ovary remained in situ, the specific hormone, and the day of the estrous cycle when treatment was performed. Present results support the idea that the ovaries send and receive neural information that is processed in the central nervous system and we propose that this information participates in controlling the secretion of gonadotropins related to the regulation of ovarian functions.